Hdac4 Regulates the Proliferation of Neural Crest-Derived Osteoblasts During Murine Craniofacial Development - Ha, Nayoung; Sun, Jian; Bian, Qian; Wu, Dandan; Wang, Xudong (Frontiers in Physiology, 2022)
Craniofacial development involves the regulation of a compendium of transcription factors, signaling molecules, and epigenetic regulators. Histone deacetylases (HDACs) are involved in the regulation of cell proliferation, differentiation, and homeostasis across a wide range of tissues, including the brain and the cardiovascular, muscular, and skeletal systems. However, the functional role of Hdac4 during craniofacial development remains unclear. In this study, we investigated the effects of knocking out Hdac4 on craniofacial skeletal development by conditionally disrupting the Hdac4 gene in cranial neural crest cells (CNCCs) using Cre-mediated recombination. Mice deficient for Hdac4 in CNCC-derived osteoblasts demonstrated a dramatic decrease in frontal bone formation. In vitro, pre-osteoblasts (MC3T3-E1 cells) lacking Hdac4 exhibited reduced proliferative activity in association with the dysregulation of cell cycle-related genes. These findings suggested that Hdac4 acts, at least in part, as a regulator of craniofacial skeletal development by positively regulating the proliferation of CNCC-derived osteoblasts.